Using multiple reference station GPS networks for category III airborne navigation - El-Mowafy, Ahmed (AcGIT, 2005)
Multiple real-time GPS reference stations (RTK Networks) were originally developed for surveying purposes to achieve cm-level positioning accuracy using a single GPS receiver. These networks can however replace the proposed airport LAAS systems for positioning during the aircraft’s precision approach and airport surface navigation. They also have the advantage of improving coverage area to include small airports. Real-time testing of this approach was carried out in Dubai, UAE, with a helicopter and a small fixed-wing aircraft using a network known as the DVRS. Results proved the idea and showed that cm to sub-meter positioning accuracy can be achieved. However, the accuracy deteriorates when temporary breaks in reception are encountered. To solve this problem, the GPS can be integrated with IMU unit, or the corrections can be predicted as a time series.